‘Rents in the Veil of Time’: Annie Besant’s Auto-biographies of Giordano Bruno - Muriel Pécastaing-Boissière (Cahiers Victoriens et Edouardiens)
Annie Besant published several autobiographical texts from 1878, starting with the preface to My Path to Atheism, when she was vice-president of the National Secular Society. Her first autobiography, Autobiographical Sketches, appeared in book form in 1885, the year she joined the Fabian Society, a decision she justified in 1886 with Why I Am a Socialist. When Besant converted to Theosophy in 1889, she wrote Why I Became a Theosophist, and her revised autobiography, Annie Besant: An Autobiography, was published in 1893, preceded by 1875 to 1891: A Fragment of Autobiography. Meanwhile, Besant penned her first biography of the Renaissance philosopher Giordano Bruno in 1876, a short sketch published in The National Reformer, the NSS weekly. She wrote a more detailed Story of Giordano Bruno, in 1884-5, at the time she joined the Socialist revival. Her fascination with Bruno took a new dimension from 1889, when she embraced the Theosophists’ belief in reincarnation: she had come to the conclusion that she had been Bruno in a past life when she lectured on Giordano Bruno: the Man and the Teacher in 1898, and delivered Le Message de Giordano Bruno au Monde moderne, in the Sorbonne in 1911. No study of Besant’s writings on Bruno has ever been published. So, this paper explores the reasons why Annie Besant wrote four biographies of Giordano Bruno between 1876 and 1911. It retraces her personal and spiritual evolution through an analysis of her biographies of Bruno as occult autobiographies, that transgress gender boundaries, and pursue the legitimization strategies developed by Besant in her openly autobiographical texts.